Characteristics of pre-ELM structures during ELM control experiment on JET with n = 2 magnetic perturbations. (29th July 2016) - Gao, Y.; Rack, M.; Liang, Y.; Sieglin, B.; Denner, P.
Abstract: Radially propagating pre-ELM (edge localized mode) structures in the heat flux profile on the outer divertor have been observed both with and without magnetic perturbations on Joint European Torus. Recently pre-ELM structures over 80% of the ELM cycle are observed. The effects of n = 2 fields on pre-ELM structures are presented and analysed in detail. Redistribution of the inter-ELM heat load with the appearances of pre-ELM structures suggest that a wider energy wetted area could be achieved by the application of n = 2 fields. The influences of q 95 and gas puffing position on the change of pre-ELM structures are studied. Pre-ELM structures are normally long lived (several milliseconds) and appear consecutively with n = 2 fields, but do not necessarily lead to an ELM crash. The experimental observations suggest that the changed magnetic topology might be a possible explanation for the propagating structures.